2018
DOI: 10.1142/s0219720018400061
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel antimicrobial peptides: A transcriptomic study of the sea anemone Cnidopus japonicus

Abstract: As essential conservative component of the innate immune systems of living organisms, antimicrobial peptides (AMPs) could complement pharmaceuticals that increasingly fail to combat various pathogens exhibiting increased resistance to microbial antibiotics. Among the properties of AMPs that suggest their potential as therapeutic agents, diverse peptides in the venoms of various predators demonstrate antimicrobial activity and kill a wide range of microorganisms. To identify potent AMPs, the study reported here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…From left to right are shown in order: peptide contig, AVP motif model results, alignment model results, composition model results, the physio-chemical model results, the overall results for the antiviral prediction, antifungal score and prediction result for the antifungal activity. www.nature.com/scientificreports/ the approach we reported is based on the use of several softwares, previously employed to perform similar analyses [49][50][51] , that exploit different algorithms for the determination of a score that predicts the biological activity of unknown peptides. We demonstrated that a similar approach can provide reliable indications about the potential biological activities of candidate AMPs, as confirmed by our preliminary tests on the antimicrobial activity of four identified AMPs ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From left to right are shown in order: peptide contig, AVP motif model results, alignment model results, composition model results, the physio-chemical model results, the overall results for the antiviral prediction, antifungal score and prediction result for the antifungal activity. www.nature.com/scientificreports/ the approach we reported is based on the use of several softwares, previously employed to perform similar analyses [49][50][51] , that exploit different algorithms for the determination of a score that predicts the biological activity of unknown peptides. We demonstrated that a similar approach can provide reliable indications about the potential biological activities of candidate AMPs, as confirmed by our preliminary tests on the antimicrobial activity of four identified AMPs ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, we aimed to go beyond the simple functional annotation which typically exclusively relies on sequence similarities to peptides deposited in public databases. Indeed, the approach we reported is based on the use of several softwares, previously employed to perform similar analyses 49 51 , that exploit different algorithms for the determination of a score that predicts the biological activity of unknown peptides. We demonstrated that a similar approach can provide reliable indications about the potential biological activities of candidate AMPs, as confirmed by our preliminary tests on the antimicrobial activity of four identified AMPs (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We do not discuss these matches further, given the lack of additional information, but it is possible that some of them represent novel toxin proteins (Table 2). Marine organisms often produce strong antimicrobial secretions on the epidermis as protection against pathogens, so nemerteans offer a novel source of potential antimicrobial peptides [38,39]. Given that A. lactifloreus is a littoral species and probably more exposed to microbial organisms, we used BLASTP (e ≤ 0.001) to screen our proteome data against the antimicrobial peptide database 3 (APD 3) [40].…”
Section: Several Secreted Proteins Are Strongly Expressed But Remain mentioning
confidence: 99%
“…Not only can antimicrobial peptides be discovered by using machine learning algorithms to analyze large quantities of data from various libraries, but recent studies have shown the potential of analyzing the toxins of various predators’ venom in order to reveal and test new antimicrobial peptides [ 39 , 40 , 41 , 42 ].…”
Section: Antimicrobial Peptides and Artificial Intelligencementioning
confidence: 99%
“…The assumed structure of peptide B3 suggested a similarity with GsMTx2, a toxin which inhibits mechanosensitive ion channels and is produced by the tarantula Grammostola spatulate. Even though the study did not manage to come up with many promising peptides that were capable of antimicrobial activity, it did show the great potential that these technologies have to discover, study, assess and test the antimicrobial activity of peptides that are found in the venom of various predators [ 39 ]. Antimicrobial peptides show great potential in targeting various strains of multi-drug-resistant bacteria, and the emergence and development of machine learning and other AI technologies can further boost research in this domain.…”
Section: Antimicrobial Peptides and Artificial Intelligencementioning
confidence: 99%